THE 60TH JUBILEE OF EVGENY V. SKLYAROV, CORRESPONDING MEMBER OF THE RUSSIAN ACADEMY OF SCIENCES - D. P. Gladkochub; R. P. Dorofeeva (Геодинамика и тектонофизика, 2015)
The article is devoted to the 60th Jubilee of Evgeny V. Sklyarov, a recognized expert in a wide variety of igneous and metamorphic processes and geodynamics. He is a Corresponding Member of the Russian Academy of Sciences, Professor, Doctor of Geology and Mineralogy, Chief Researcher of Laboratory of Paleogeodynamics in IEC SB RAS, and Chief Editor of Geodynamics and Tectonophysics.